The Effect of Job Stress on Employees Engagement with Mindfulness as a Moderation Variable: (Study of Gen Z Employees in the Coffee Shop Industry, Bandar Lampung) - Mela Malidha; Ribhan Ribhan; Yuningsih Yuningsih; Nova Mardiana (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Workers in Bandar Lampung's coffee shop sector are particularly susceptible to stress. The purpose of this study is to ascertain how job stress affects employee engagement while controlling for mindfulness. Stress at work is the independent variable that is employed. Employee involvement is employed as the dependent variable. Mindfulness is the moderating variable employed. All of the Generation Z workers in the Bandar Lampung coffee shop sector made up the study's demographic. Purposive sampling was the technique employed, and the sample size consisted of 133 workers from coffee shops. A Likert-scaled questionnaire was employed as the data collection tool in this investigation. Simple linear regression and moderation regression analysis are used in this research analysis technique. The study's findings suggest that work stress has a substantial and detrimental impact on employee engagement and that mindfulness does not mitigate this effect in the case of Generation Z workers in Bandar Lampung's coffee shop sector. The study's conclusion is that the coffee shop should focus more on the responsibilities assigned to its staff members' tasks and modify the workload in accordance with their skill levels. The coffee shop has to learn more about the needs that its employees have at work.